Photoelectrochemical investigations of thermally formed films on titanium surfaces - Mickova, Irena (Society of Chemists and Technologists of Macedonia, 2009)
The semi-conducting and photoelectrical properties of TiO2 films prepared with thermal oxidation of titanium in the temperature range from 200 to 600 degrees C were studied. Short theoretical background for application of photocurrent in semiconductor electrochemistry was presented. For all investigated temperatures and times of thermal treatments the semi-conducting properties as photocurrent peaks and band gap energies were determined. At lower temperatures the anodic values of photocurrent peaks confirmed the existence of n-type semiconducting TiO2 films with amorphous structure. With increasing the temperature and time of thermal treatment the development of crystalline structure in the film is followed with small decreasing of band gap energy. For films formed at higher temperatures and longer time of thermal treatment the determined band gap energies are close to the 3 eV that corresponds to the rutile structure of the film.
Keywords: TiO2 films; semiconductor; photocurrent; rutile structure